LANGUAGE REVITALIZATION THROUGH EDUCATION: PRESERVING INDIGENOUS TONGUES IN THE DIGITAL ERA (Eureka Journal of Language, Culture & Social Change, 2025)
Indigenous languages across the globe face rapid decline due to globalization and linguistic homogenization. Education systems have a central role to play in reversing this trend. This paper explores the intersection of digital technology, education policy, and community-based initiatives in revitalizing indigenous tongues. Through case studies from Asia, Africa, and Latin America, the research highlights the success of digital literacy programs and culturally responsive curricula in promoting language sustainability. Findings suggest that integrating indigenous languages into both formal education and digital spaces can transform attitudes and ensure long-term preservation.
Keywords: Language Revitalization, Indigenous Languages, Educational Policy, Digital Learning, Linguistic Diversity.